The Singapore convention on mediation - A brighter future for Asian dispute resolution - CHUA, Eunice (Institutional Knowledge at Singapore Management University, 2019)
On 26 June 2018, the UnitedNations Commission on International Trade Law (UNCITRAL) approved, largelywithout modification, the final drafts of the Convention on International SettlementAgreements Resulting from Mediation (the Singapore Convention) and amendmentsto the Model Law on International Commercial Mediation prepared by WorkingGroup II. These instruments aim to promote the enforceability of internationalcommercial settlement agreements reached through mediation in the same way thatthe New York Convention facilitates the recognition and enforcement ofinternational arbitration awards. This paper provides a critical analysis of theSingapore Convention and some commentary from an Asian perspective.